Space of SO (3)-orbits of elasticity tensors - Bóna, A.; Bucataru, I.; Slawinski, M.A. (Archives of Mechanics, 2008)
We construct an eighteen-dimensional orbifold that is in a one-to-one correspondence with the space of SO (3)-orbits of elasticity tensors. This allows us to obtain a local parametrization of SO (3)-orbits of elasticity tensors by six SO (6)-invariant and twelve SO (3)-invariant parameters. This process unravels the structure of the space of the orbits of the elasticity tensors.